Respuesta :

9514 1404 393

Answer:

  b.  9^(x-3) = 9^3

Step-by-step explanation:

Realizing that 729 = 9^3, we can rewrite the equation ...

  9^(x -3) = 729

as ...

  9^(x -3) = 9^3 . . . . . . matches the second selection

__

Recognizing that 9 = 3^2, a couple of other equivalent forms can be made.

  (3^2)^(x -3) = (3^2)^3

  3^(2x-6) = 3^6

or, taking the square root, ...

  3^(x -3) = 3^3

None of these forms match any answer choices.

_____

The solution will be found by matching exponents:

  x -3 = 3

  x = 6

ACCESS MORE